Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (Dau), Dana Bagi Hasil (DBH), Dan Fiscal Stress terhadap Tingkat Kemandirian di Provinsi Kalimantan Selatan - Prasetyo, Aryadhani; Rahayu, Dewi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted to (1) analyze the effect of Regional OriginalRevenue, General Allocation Funds, Profit Sharing Funds and Fiscal Stress that affectthe level of independence both simultaneously and partially in the Province of SouthKalimantan; (2) to analyze what are the most dominant variables affecting the level ofindependence in the province of South Kalimantan.The data obtained in this study is from the official website of the SouthKalimantan Provincial Government, namely the Central Kalimantan Statistics Agency,which deals with the South Kalimantan Provincial Government Financial Report and the2002-2016 Budget Realization Report, which is available in BPS publication dataentitled South Kalimantan in Figures.The results of the study show that (1) Local Revenue, General Allocation Funds,Profit Sharing Funds, and Fiscal Stress have an effect on the level of independencesimultaneously; (2) Regional Original Income dan Profit Sharing Funds affect the Levelof Independence; (3) General Allocation Funds and Fiscal Stress have no significanteffect on the Level of Independence; and (4) Regional Original Income is the mostdominant variable that affects the Level of Independence.